What can a low-cost fish-finder tell us about the seabed? - Sanchez Carnero, Noela Belen (2018)
Low-cost non-scientific echosounders are commonly used for safety and other non-scientific purposes. These echosounders routinely record data which are rarely processed for later use, but which could provide interesting information about the seabed. In this work, we report on the use of a low-cost echosounder for bottom classification in five coastal rocky reefs of northern Argentine Patagonia. Underwater video transects were acquired over the same area as the acoustic data, in order to compare acoustic and visual classifications at or near the points where acoustic and video transects intersected (crossing sites). The reliability of these validation points decreases with the distance between the acoustic data points and the video transects as well as with the habitat heterogeneity as observed in the video. The shape of the depth-corrected acoustic echoes allowed easy discrimination between hard (or rocky) and soft (or muddy) bottoms by using a linear function as threshold optimized from a training set of crossing sites. The classification accuracy obtained using only validation points classified as most reliable was 96% (Cohen's kappa coefficient κ = 0.88, indicating nearly perfect agreement). These results show that this low-cost methodology offers a suitable alternative to using scientific echosounders for mapping rocky-reef areas.